2022
DOI: 10.1002/anie.202116870
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Tail‐to‐Tail Reductive Dimerization of Terminal Alkynes to 2,3‐Dibranched Butadienes

Abstract: The palladium‐catalyzed tail‐to‐tail reductive dimerization of terminal alkynes is described for the first time. Aromatic terminal alkynes bearing diverse and sensitive functional groups as well as aliphatic terminal alkynes are efficiently transformed to 2,3‐dibranched butadienes. The key to achieve a selective tail‐to‐tail reductive dimerization reaction is to control appropriately the acidity of the reaction solution, which is accomplished by a combined use of pivalic acid and para‐toluenesulfonic acid. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…13 C­{ 1 H} NMR (126 MHz, chloroform- d ): δ 166.8, 148.6, 144.3, 129.6, 129.3, 127.4, 118.3, 52.1. The NMR data were consistent with those reported …”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…13 C­{ 1 H} NMR (126 MHz, chloroform- d ): δ 166.8, 148.6, 144.3, 129.6, 129.3, 127.4, 118.3, 52.1. The NMR data were consistent with those reported …”
Section: Methodssupporting
confidence: 91%
“…The NMR data were consistent with those reported. 40 4,4′-(Buta-1,3-diene-2,3-diyl)bis((trifluoromethoxy)benzene) (1q). 4,4′-(Buta-1,3-diene-2,3-diyl)bis((trifluoromethoxy)benzene) (1q) was prepared from methyl 1-(4-(trifluoromethoxy)phenyl)ethan-1-one (2.0 g, 10.0 mmol).…”
Section: 4′-(buta-13-diene-23-diyl)bis(isopropylbenzene) (1ementioning
confidence: 99%
“…We can see that aryl bromides performed worse than the corresponding aryl triflates in all of the three cases. It is deduced that the higher yield of aryl triflates would be ascribed to their higher reactivity, while the more excellent regio -selectivity to vinyl C–H arylation would be attributed to the ionic nature of the resulting aryl palladium triflate generated via oxidative addition . It is reported that CsOPiv is essential to the previous aryl halide-based Pd shift/vinyl C–H activation strategy .…”
Section: Resultsmentioning
confidence: 99%
“…In 2022, Bao and Li reported a palladium-catalyzed tail-to-tail reductive dimerization of terminal alkynes to synthesize 2,3-dibranched butadienes for the first time (Scheme 12(a)). 61 The formation of alkenyl palladium intermediate under acidic conditions plays an essential role in delivering diene products. The C–C coupling between alkene and alkyne is also explored to prepare conjugated diene.…”
Section: Metal-catalyzed Markovnikov-type Selective Hydrofunctionaliz...mentioning
confidence: 99%